2011
DOI: 10.1021/pr200304u
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Proteomic Metrics of Low Abundance Proteins through Proteome Equalization Using ProteoMiner Prior to MudPIT

Abstract: Ideally shotgun proteomics would facilitate the identification of an entire proteome with 100% protein sequence coverage. In reality, the large dynamic range and complexity of cellular proteomes results in oversampling of abundant proteins, while peptides from low abundance proteins are undersampled or remain undetected. We tested the proteome equalization technology, ProteoMiner, in conjunction with Multidimensional Protein Identification Technology (MudPIT) to determine how the equalization of protein dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…The enrichment for shorter proteins can be appreciated in the upper left panel of Figure 3B. Lowabundance proteins were targeted using ProteoMiner (Guerrier et al 2008;Fonslow et al 2011). These experiments (Fig.…”
Section: Identification Of the Complete Expressed B Henselae Proteomementioning
confidence: 99%
“…The enrichment for shorter proteins can be appreciated in the upper left panel of Figure 3B. Lowabundance proteins were targeted using ProteoMiner (Guerrier et al 2008;Fonslow et al 2011). These experiments (Fig.…”
Section: Identification Of the Complete Expressed B Henselae Proteomementioning
confidence: 99%
“…For very complex extracts like eukaryotic cell lysates, Fonslow et al (2011) found that the addition of 0.1% SDS allows increasing the number of captured proteins and hence the number of spots found by 2D gel analysis. These authors justified this approach based on the assumption that this detergent denatures proteins and further exposes high-affinity epitopes, disrupts protein interactions within protein complexes, and may minimize hydrophobic hexapeptide-protein interactions.…”
Section: Suggested Detergents and Variantsmentioning
confidence: 99%
“…However, if the objective is limited to identification of captured proteins by means of the analysis of peptides, it is possible to hydrolyze the captured proteins directly on the beads (Fonslow et al, 2011;Meng et al, 2011). This approach is also recommended when the volume of beads is very small.…”
Section: On-bead Digestionmentioning
confidence: 99%
“…Proteomic analysis can be carried out using a variety of approaches, depending on expertise and availability of equipment. When the protein content is low, a gel-free strategy of direct on-beads digestion can be employed and the resulting tryptic peptides can be analyzed by MudPIT nano-LC-MS/ MS [ 22 ]. The resultant MS/MS data can be investigated with the latest version of the Arabidopsis protein database using Mascot (Matrix Sciences).…”
Section: Notesmentioning
confidence: 99%